THE EFFECTS OF ENVIRONMENTAL FACTORS ON THE DYNAMIC GROWTH PATTERN OF MANGROVE Avicennia marina - Endah Dwi Hastuti; Sutrisno Anggoro; Rudhi Pribadi (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Avicennia marina is a species of mangrove tree occurs in the intertidal zones of estuarine areas in Asia, including Indonesia. Mangrove within the genus member of Avicennia have long dominated many coastal areas along Semarang and Demak coasts. The aim of this research was to analyze the effect pattern of several environment parameters to Avicennia seedling growth rate. Observation was held by setting 8 stations with 3 transects, each including mangrove survey and environment parameter measurements. Mangrove survey including seedling and sapling stage occupying 1 x 1 m and 5 x 5 m transect plot respectively. While environmental factor measurements including on site measurement for temperature, salinity, pH and DO and laboratory analysis for organic matter, nutrient (N,P,K) and sediment structure. The results showed there were 2 effect pattern for environmental parameters observed including polynomial quadratic and logarithmic patterns. Parameters which had polynomial quadratic pattern including salinity, DO, P, sand and silt, while parameters which had logarithmic pattern were temperature, pH, organic matter and N.